Isolation and Identification of Mold Contaminants in Peanut Paste from the Cengkareng Market of West Jakarta - Alfriana Margareta; Anis Setyowati (Jurnal EduHealth, 2023)
The filamentous molds associated with peanut paste produce biochemicals known as mycotoxins. The major mycotoxins are aflatoxins produced by molds from the genera Aspergillus and Penicillium. Mold contaminants can be occurred due to poor hygiene storage. The purpose of this study was to determine the presence of molds in peanut paste sold at the Cengkareng market in order to assist people in being attentive to the storage conditions of peanut paste. Samples were collected randomly with a total of 15 packages of peanut paste from Cengkareng market, West Jakarta, Indonesia. Potato Dextrose Agar was used for the isolation and identification of molds. The molds were observed based on the morphological features through macroscopic and microscopic examination. The frequencies of 15 samples contaminated with molds were computed on a percentage. From the observed morphological features and colony colour of molds, those were A. niger, A. flavus, Penicillium sp, and Mucor sp. This research also revealed that of the 15 samples identified, A. niger and A. flavus, 40% respectively. Other species Penicillium sp. 27% and Mucor sp. 13% were the least common. Therefore, this study confirmed that Aspergillus is the highest risk of contaminating peanut paste compared to other genera, which can cause a health problem for humans.